Discovery and optimization of pyrazole amides as antagonists of CCR1. Issue 3 (1st February 2019) - Harcken, Christian; Sarko, Christopher; Mao, Can; Lord, John; Raudenbush, Brian; Razavi, Hossein; Liu, Pingrong; Swinamer, Alan; Disalvo, Darren; Lee, Thomas; Lin, Siqi; Kukulka, Alison; et al.
Graphical abstract: Highlights: A HTS screen for CCR1 antagonists afforded a novel hit containing a pyrazole core. Multi parameter optimization led to advanced candidate compounds. Candidates show 250-fold improved CCR1 potency compared to initial hit. Candidates show excellent off-target selectivity, attractive drug-like properties. Abstract: A HTS screen for CCR1 antagonists afforded a novel sub-micromolar hit 5 containing a pyrazole core. In this report the design, optimization, and SAR of novel CCR1 antagonists based on a pyrazole core motif is presented. Optimization led to the advanced candidate compounds ( S )-16q and ( S )-16r with 250-fold improved CCR1 potency, excellent off-target selectivity and attractive drug-like properties.